A critical analysis of Bristol Airport's employee surface access habits: Developing strategic recommendations for reducing private vehicle usage. (June 2022) - Risby, James; Guest, Sam; Warnock-Smith, David
Abstract: Bristol Airport is a regional airport based in the South West of England. It has plans to increase capacity from 10 to 12 million passengers per annum. The airport has planning obligations with North Somerset Council, which include obligations on air quality. One of the airport's challenges relates to surface access and reducing the use of single occupancy vehicles. This challenge is shared among most airports globally, many of whom have sought to pinpoint the factors influencing this usage. This research aimed to find the contributing factors affecting users at Bristol Airport with a particular focus on employees to make strategic recommendations. A mixed method approach, through the use of questionnaires and an employee specific focus group led to findings that indicated common factors among employees namely convenience and reliability as the main influences reducing the stress of travel. There were secondary factors such as cost, and family commitments, which was the main differentiator between employee and passenger choice factors as evidenced in the literature. The number of meaningful strategic interventions at Bristol was found to be limited. There is some evidence pointing to the potential popularity of airport employee incentive schemes such as the use of discounted hybrid cars. This would help reduce emissions but not single occupancy private vehicle usage. This research provides Bristol Airport with firm grounds to continue investigating the plethora of factors and possible sustainable strategies to meet their environment related planning obligations.